Tuvalu : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Tuvalu. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that the macroeconomic outlook for Tuvalu is stable. Real GDP growth in 2015 is estimated at 2.6 percent and is projected to rise to 4 percent in 2016 owing to several large infrastructure projects and recovery spending following Cyclone Pam. Inflation remained steady in 2015 at 3.2 percent. The fiscal position is expected to turn into a small deficit in 2016 and is projected to remain in deficit over the medium term. Risks to the outlook relate to the effects of climate change, volatility in fishing revenues, and volatile global financial conditions, which could affect distributions to the budget from the Tuvalu Trust Fund.